Telaah Penafsiran Muḥammad Syaḥrūr Terhadap Ayat Kewarisan 2:1 - Aniroh, Reni Nur (SUHUF, 2014)
The most crucial issue in islamic heritance is inheritance formula 2:1 that assessed gender bias. The traditional interpretation claims that males always receive twice the amount of female shares. However, Syaḥrūr’s interpretation concludes that this verse can be understood dynamically and has alternative of interpretation. Syaḥrūr also complements the methodology with the tools of modern mathematic. This makes his interpretation be unique and wonderfull, but also controversial. Some people give praise and deep admiration, while others object and give him a bad reputation. This paper would like to analyze Syaḥrūr’s interpretation about inheritance verse 2:1 and than analyze whether the accusations to him is rights or wrongs. Keywords: inheretance verse 2:1, modern mathematic, Muḥammad Syaḥrūr interpretation.